Advertisement Remove all ads

If P (5, R) = P (6, R − 1), Find R ? - Mathematics

If P (5, r) = P (6, r − 1), find r ?

Advertisement Remove all ads

Solution

P (5, r) = P (6, r − 1)
or  5Pr = 6Pr-1

\[\frac{5!}{\left( 5 - r \right)!} = \frac{6!}{\left( 6 - r + 1 \right)!}\]
\[ \Rightarrow \frac{\left( 6 - r + 1 \right)!}{\left( 5 - r \right)!} = \frac{6!}{5!}\]
\[ \Rightarrow \frac{(7 - r)!}{\left( 5 - r \right)!} = \frac{6\left( 5! \right)}{5!}\]
\[ \Rightarrow \frac{\left( 7 - r \right)\left( 6 - r \right)\left( 5 - r \right)!}{\left( 5 - r \right)!} = 6\]
\[ \Rightarrow \left( 7 - r \right)\left( 6 - r \right) = 6\]
\[ \Rightarrow \left( 7 - r \right)\left( 6 - r \right) = 3 \times 2\]
\[\text{On comparing the above two equations, we get}: \]
\[7 - r = 3\]
\[ \Rightarrow r = 4\]

Concept: Factorial N (N!) Permutations and Combinations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 16 Permutations
Exercise 16.3 | Q 2 | Page 28
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×